The effect of gradient order on mechanical behaviors of gradient nanotwinned Cu. (15th April 2019) - Cheng, Zhao; Lu, Lei
Abstract: Here this paper reports the gradient order effect on deformation behaviors of gradient nanotwinned (GNT) Cu samples with the same structural gradient. Tension tests indicated that the GNT Cu with normal gradient order (hard surfaces and soft core) exhibits a higher strength and a lower surface roughening during deformation than those of the GNT Cu with reverse gradient order (soft surfaces and hard core). By systematic comparison to the lateral strain and surface morphologies, it was revealed that the normal gradient order contributes to a larger strain gradient and a stronger constraint during the plastic deformation. Graphical abstract: Unlabelled Image